A Systematic and Critical Review of Parental Program Integrated to Prevent and Manage Delay Development in Children - Rian Adi Pamungkas; Kanittha Chamroonsawasdi; Andi Mayasari Usman; Widia Sari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Delay development is a crucial problem in the early childhood period. An effective parental program is an essential strategy to prevent and manage delayed development. However, limited number studies described how parental integrated to prevent and manage delay development systematically. This review aims to describe developmental delays and explore strategies for their prevention and management in early childhood. Method: A total of 1,237 articles were extracted from four databases including, PubMed, Scopus, and Web of Science, using suitable keywords as; "parenting-based program," "delay development," "early childhood," and "parenting style." The appraisal of the systematic review was based on the PRISMA format. Result: This review described four domains of developmental delays among childhood, such as physical, cognitive, language and social, and emotional development. There were nine tools for early childhood developmental screening. The effective parental program focused on the problem-solving, positive parent-child relationship, quality of communication, coaching the child, and stimulating the home learning environment. Conclusion: Effective management suggested positive of the parental program on improvement of child development and child behaviors and improvement of antisocial personality. From the findings, healthcare providers should promote a parental-based program to prevent and manage the delayed development of the early childhood period.